Lending for Growth? An Analysis of State-Owned Banks in China - Fredrik N. G. Andersson; Katarzyna Burzynska; Sonja Opper (Lund University, School of Economics and Management, Department of Economics, 2013)
This paper provides the first comparative analysis of different types of publicly owned banks operating in China between 1997 and 2008. Using principal component analysis and Granger-causality tests, this study shows that China's state-owned commercial banks and rural credit cooperatives did not promote GDP growth during the observation period. State-owned commercial banks even had a negative effect on growth in the manufacturing sector. By contrast, state policy banks and joint stock commercial banks did promote domestic growth. China's experience presents a more nuanced picture of state banking that goes beyond the role of ownership to consider functional and institutional differences.
Keywords: G21; O16; P30; 330; China; Banking sector; Economic growth